Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1021/acs.jafc.5b04710
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variability in Pesticide Exposure Downstream of a Heavily Irrigated Cropping Area: Application of Different Monitoring Techniques

Abstract: 23Pesticide exposure threatens many freshwater and estuarine ecosystems around the world. 24This study examined the temporal and spatial trends of pesticide concentrations in a 25 waterway within an agriculturally developed dry-tropics catchment using a combination of 26 grab and passive sampling methods over a continuous two year monitoring program. A total 27 of 43 pesticide residues were detected with seven pesticides exceeding ecologically relevant 28 water quality guidelines/trigger values during the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 37 publications
0
37
0
1
Order By: Relevance
“…Regular monitoring of pesticides in the GBR has found that exceedances of WQGVs by individual herbicides in the GBR marine waters occur only occasionally 15,16,24 ; however, approximately 80% of the water samples collected in the GBR catchment area between 2011 and 2015 contained mixtures of up to 20 pesticides with two to four modes of action 29 . Consequently, there is a strong likelihood of additivity or synergistic interactions between multiple herbicides, and the total toxicity of herbicide mixtures should be considered in monitoring programs and for risk assessments 14,[30][31][32] .…”
mentioning
confidence: 99%
“…Regular monitoring of pesticides in the GBR has found that exceedances of WQGVs by individual herbicides in the GBR marine waters occur only occasionally 15,16,24 ; however, approximately 80% of the water samples collected in the GBR catchment area between 2011 and 2015 contained mixtures of up to 20 pesticides with two to four modes of action 29 . Consequently, there is a strong likelihood of additivity or synergistic interactions between multiple herbicides, and the total toxicity of herbicide mixtures should be considered in monitoring programs and for risk assessments 14,[30][31][32] .…”
mentioning
confidence: 99%
“…Other effects in nontarget species exposed to chlorpyrifos include reduced settlement and metamorphosis of coral larvae (Markey et al 2007), as well as decreased hatching success (Mhadhbi and Beiras 2012) and muscle cholinesterase activity in fish (Botte et al 2012). Considering the intense use of atrazine and chlorpyrifos in agriculture and the fact that they often co‐occur in aquatic environments (Shaw et al 2010; Smith et al 2012; O'Brien et al 2016), research on potential interactive effects of these pesticides in marine species is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Successive Australian government programs have aimed to reduce the loads of pesticides entering waters of the GBR and its catchments (Brodie et al 2017;RWQIP 2018). At the same time, there have been changes in regulations and registration for pesticide application in coastal agriculture (Davis et al 2014), leading to shifts in usage patterns and to at least 44 "alternative" pesticides being detected in the GBR catchments and lagoon (King et al 2013;O'Brien et al 2016). For example, the insecticides chlorothalonil, fipronil and propiconazole have been detected in the catchments while imidacloprid and diazinon have been found in both the catchments and GBR lagoon (Devlin et al 2015;O'Brien et al 2014).…”
Section: Alternative Pesticides In the Gbrmentioning
confidence: 99%